Logarithmic doublets in CCFT - Agnese Bissi; Laura Donnay; Beniamino Valsesia (Journal of High Energy Physics)
Abstract We investigate the presence of logarithmic CFT doublets in the soft sector of celestial CFT related with supertranslations. We show that the quantum operator associated with a log u late-time behavior for the asymptotic gravitational shear forms a logarithmic CFT pair of conformal dimension ∆ = 1 with an IR-regulated supertranslation Goldstone current. We discuss this result in connection with previous encounters of log CFT structures in the IR-finite part of celestial OPEs.